Pengaruh motivasi terhadap minat mahasiswa akuntansi untuk mengikuti pendidikan profesi akuntansi (ppak) - Sri Wahyuni; Zirman '; Riska Natariasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to look at the effect of motivation on student interest in accounting education to follow the accounting profession.This study was conducted by taking a sample of 100 students of accounting faculty of economics University of Riau, and the State Islamic University of Riau Islamic University class of 2009 and 2010. The sampling was based on a purposive sampling method. Data from this study are then processed using multiple regression analysis through SPSS 17 statistical applications.The results of this study indicate that the quality and motivation motivation significantly affect the economic interest of the education of accounting students to follow the accounting profession (PPAk). While the career motivation not significantly affect the interest of the education of accounting students to follow the accounting profession (PPAk). The coefficient of determination (R2) in this study was 0.245. this suggests that the effect of independent variables on the dependent 24.5% and the remaining 75.5% is influenced by other variables.Key Word : Quality Motivation , Career Motivation, Economic Motivation and Interest To Follow The Accounting Profession Education (PPAk)